ENERGY AUDIT FOR THE ELECTRICAL SYSTEM IN THE COMMERCIAL BUILDING - Amiral Aziz; Rizka Elyza Sari (website, 2008)
ABSTRACT ENERGY AUDIT FOR THE ELECTRICAL SYSTEM IN THE COMMERCIAL BUOLDING . This papers presents some results of the energy audit that was conducted in the commercial building i.e a hotel to recommended measures to decrease energy costs every month by identifying of energy loss. This audit focused on the electrical system. The performance of this system was examined to identify opportunities for improving energy efficiency. It is concluded that approximately 65 % of electricity use in the object study is for its central air conditioning system. Therefore, automatic energy saving adjustments towards the air conditioning system will provide a significant amount of savings. Keywords: Energy audit, electrical system ABSTRAK AUDIT ENERGI UNTUK SISTEM ELEKTRIKAL PADA GEDUNG KOMERSIAL. Tulisan ini menampilkan beberapa hasil dari audit energi yang telah dilakukan untuk gedung komersial dalam hal ini hotel untuk menurunkan biaya energi setiap bulan dengan cara mengidentifikasi kehilangan energi. Audit ini difokuskan pada system elektrikal. Kinerja system ini telah dievaluasi untuk mengidentifikasi oportunitas memperbaiki efisiensi energy. Disimpulkan bahwa sekitar 65 % dari penggunaan energi pada objek studi adalah untuk system pengkondisian udara sentral. Oleh karena itu, pengaturan penghematan energi otomatis pada system pengkondisian udara akan memberikan jumlah yang cukup siknifikan. Kata Kunci : Audit energi, sistem elektrikal